Direct Supervision of Daily Consumption of Blood Supplement Tablets During Menstruation Can Increase Adolescent Hemoglobin Levels - Depi Susen Dewi; Asmawati Asmawati; Erni Buston; Rahma Annisa (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2023)
Consumption of blood supplement tablets (TTD) during menstruation is one effort to prevent anemia. The Ministry of Health recommends taking one tablet supplements weekly and one tablet daily during menstruation. However, adherence of TTD consumption still low among adolescence. The purpose of this study was to determine the effect of direct supervision of tablets consumption on hemoglobin level of adolescent girls. This research is a quasi-experimental with pretest-post-test with control group. Samples are female students of Islamic Boarding School at Bengkulu City. A total sample of 56 female students consisting of 28 intervention group and 28 control group was taken by systematic random sampling. Data were analyzed using t-test. TTD were given every day during menstruation until 2 months. Hemoglobin levels baseline were measured at the first day after menstruation and post HB level were measured at the third month of menstruation. The results showed that the baseline of mean HB in intervention group was 12.2 gr and control group was 12.74 gr and after intervention, the mean of HB increases in intervention group by 1.13 gr and in control group by 0.4 gr. There was a difference in average of hemoglobin levels before and after intervention between the two groups, the difference was 0.79 gr (p 0.000 < α 0.005). Supervision of TTD consumption by the closest person like teacher was important for students, it can promote adherence of TTD consumption, which can increase HB levels and lower anemia among adolescent.